2019
DOI: 10.5114/aoms.2019.89449
|View full text |Cite
|
Sign up to set email alerts
|

Is type 2 diabetes mellitus a coronary heart disease equivalent or not? Do not just enjoy the debate and forget the patient!

Abstract: A b s t r a c tIn the last several years there has been a large debate whether patients with type 2 diabetes (T2DM) should be treated as those with high or very high cardiovascular risk, and whether T2DM should be considered as equivalent to coronary heart disease (CHD). It all started in the 2001 in National Cholesterol Education Program -Adult Treatment Panel III recommendations, and the knowledge has changed on this issue at least several times. But the main problem is that due to these inconsistencies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Diabetes mellitus is associated with a 2- to 4-fold higher risk of CVD events [ 56 ]. Moreover, patients with longstanding DM (≥ 10 years), and without CVD, may be comparable to coronary heart disease (CHD) patients without DM in terms of future CHD events [ 57 , 58 ]. Therefore, the above-mentioned result is clinically plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is associated with a 2- to 4-fold higher risk of CVD events [ 56 ]. Moreover, patients with longstanding DM (≥ 10 years), and without CVD, may be comparable to coronary heart disease (CHD) patients without DM in terms of future CHD events [ 57 , 58 ]. Therefore, the above-mentioned result is clinically plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Data from multiple studies indicate that patients with diabetes who experience MI have a more advanced coronary atherosclerosis and worse short-and long-term outcomes, than the non-diabetic MI patients [30][31][32][33]. The pooled results of the randomized trials, as well as from the Global Registry of Acute Coronary Events (GRACE) registry, indicate that in patients with either non-ST segment acute coronary syndrome (NSTE-ACS) or STEMI, risk of death at short-and medium-term follow-up, is significantly higher in the presence of diabetes [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that 51% of our patients were diabetic, which was approved by Katsiki et al, who stated that diabetes mellitus is associated with increased prevalence of cardiovascular disease. Indeed, diabetic patients have a 2 -4-fold higher risk for CVD morbidity and mortality than healthy non-diabetics [12].…”
Section: Discussionmentioning
confidence: 99%